SUSTAINABLE BUSINESS DEVELOPMENT: POST-WAR PRIORITIES - KULHANIK, Oksana; NAHORNYI, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article identifies the key priorities of sustainable business development in the context of post-war reconstruction of Ukraine. The study analyzed indicators of the current state of business, in particular the index of business activity expectations, which showed a slight improvement in the business environment, despite the impact of various macroeconomic factors. The author also characterizes the state of business functioning in Ukraine during the war, which indicates the possibility of a rapid recovery of key sectors of the economy due to balanced decisions by the state. The author analyzes regional peculiarities in the field of entrepreneurship that are directly related to the intensity of hostilities. In the course of forming the theoretical basis for the topic, the author analyzes the literature and, on their basis, formulates the concept of "sustainable development", which involves the implementation of measures for economic, social and environmental growth to improve public welfare and the natural environment. In addition, the components of the three-factor model of sustainable development are identified. In this context, the author characterizes the economic factor, which includes providing the country with its own resources, using financial and economic levers, and forming investment programs. The factor of social development includes ensuring public safety, rational use of natural resources, reproduction of human resources and development of education. The article identifies aspects of the environmental component of sustainable development, namely, the introduction of environmental standards for construction, resource management, energy efficiency, and reduction of natural resource consumption. The measures aimed at ensuring sustainable development include the need to restore solvency, modernize production facilities, introduce environmental technologies, etc. by expanding international relations.
Keywords: sustainable development; post-war reconstruction; business sector; business environment; economic stability; energy efficiency; environmental technologies; socialization; socialization of business